2021
DOI: 10.1177/0308518x211034177
|View full text |Cite
|
Sign up to set email alerts
|

Searching for housing in the digital age: Neighborhood representation on internet rental housing platforms across space, platform, and metropolitan segregation

Abstract: Understanding residential mobility, housing affordability, and the geography of neighborhood advantage and disadvantage relies on robust information about housing search processes and housing markets. Existing data about housing markets, especially rental markets, suffer from accuracy issues and a lack of temporal and geographic flexibility. Data collected from online rental platforms that are commonly used can help address these issues and hold considerable promise for better understanding the full distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We focus on listings posted to these two sites because qualitative studies of housing search processes in multiple metropolitan areas indicate that voucher holders use online listings from Craigslist and gosection8.com (Greif 2018; Harvey et al 2020; Metzger et al 2019). In addition, Craigslist is widely recognized as the most comprehensive platform for today’s metropolitan rental housing market, which overwhelmingly operates online (Boeing and Waddell 2017; Hess et al 2021; Kroft and Pope 2014; Kuk et al 2021; Schachter and Besbris 2017). The number of novel ads for rental housing on Craigslist has far outpaced any other source in many U.S. cities for over a decade, and Internet sites like Craigslist have become one of the most common ways renters find their housing—particularly renters with families and low levels of education (Besbris et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on listings posted to these two sites because qualitative studies of housing search processes in multiple metropolitan areas indicate that voucher holders use online listings from Craigslist and gosection8.com (Greif 2018; Harvey et al 2020; Metzger et al 2019). In addition, Craigslist is widely recognized as the most comprehensive platform for today’s metropolitan rental housing market, which overwhelmingly operates online (Boeing and Waddell 2017; Hess et al 2021; Kroft and Pope 2014; Kuk et al 2021; Schachter and Besbris 2017). The number of novel ads for rental housing on Craigslist has far outpaced any other source in many U.S. cities for over a decade, and Internet sites like Craigslist have become one of the most common ways renters find their housing—particularly renters with families and low levels of education (Besbris et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, they prioritize unit features over less known neighborhood qualities (DeLuca et al 2013;DeLuca and Rosenblatt 2017;Rosenblatt and DeLuca 2012). Under these circumstances, housing advertisements that mention the acceptance or denial of vouchers may be especially strong signals about the appropriateness of a particular unit (see Besbris, Schachter, and Kuk 2021;Boeing et al 2021;Kennedy et al 2021), and past research has shown that restricted search conditions and fear of discrimination lead voucher holding households to scan rental advertisements specifically for positive or welcoming language (Rosenblatt and Cossyleon 2018).…”
Section: Voucher Holders' Residential Outcomesmentioning
confidence: 99%